Fast Diffusion Sustains Plasma Membrane Accumulation of Phosphatase of Regenerating Liver-1 - Castro-Sánchez, Patricia; Hernández-Pérez, Sara; Aguilar-Sopeña, Oscar; Ramírez-Muñoz, Rocia; Rodríguez-Perales, Sandra; Torres-Ruiz, Raúl; Roda-Navarro, Pedro (Frontiers in Cell and Developmental Biology, 2020)
It has been proposed that the accumulation of farnesylated phosphatase of regenerating liver-1 (PRL-1) at the plasma membrane is mediated by static electrostatic interactions of a polybasic region with acidic membrane lipids and assisted by oligomerization. Nonetheless, localization at early and recycling endosomes suggests that the recycling compartment might also contribute to its plasma membrane accumulation. Here, we investigated in live cells the dynamics of PRL-1 fused to the green fluorescent protein (GFP-PRL-1). Blocking the secretory pathway and photobleaching techniques suggested that plasma membrane accumulation of PRL-1 was not sustained by recycling endosomes but by a dynamic exchange of diffusible protein pools. Consistent with this idea, fluorescence correlation spectroscopy in cells overexpressing wild type or monomeric mutants of GFP-PRL-1 measured cytosolic and membrane-diffusing pools of protein that were not dependent on oligomerization. Endogenous expression of GFP-PRL-1 by CRISPR/Cas9 genome edition confirmed the existence of fast diffusing cytosolic and membrane pools of protein. We propose that plasma membrane PRL-1 replenishment is independent of the recycling compartment and the oligomerization state and mainly driven by fast diffusion of the cytosolic pool.